2003
DOI: 10.1055/s-2003-42588
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Venous Thromboembolism in Children

Abstract: Venous thromboembolic events (VTE) in children are mostly related to central venous lines (CVL), and are located in the central upper venous system. The incidence of VTE in children with CVL is significant. However, the majority of CVL-related VTE do not present with typical symptoms or are not recognized due to underlying disease. Asymptomatic VTE still cause significant venous obstruction and are associated with short-term and long-term clinical complications. Because the clinical diagnosis of CVL-related VT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(9 citation statements)
references
References 95 publications
0
9
0
Order By: Relevance
“…Most importantly, reported incidences of CVC-VTE depend on clinical awareness and the diagnostic test used to investigate for VTE. Incidences of CVC-VTE in children identified through clinical diagnosis were 4–13% (5–7), through venous ultrasonographic screening were 1–44% (5), and screening via venography were 13–50% (68). Table 1 highlights CVC characteristics that may lead to an increased VTE rate.…”
Section: Resultsmentioning
confidence: 99%
“…Most importantly, reported incidences of CVC-VTE depend on clinical awareness and the diagnostic test used to investigate for VTE. Incidences of CVC-VTE in children identified through clinical diagnosis were 4–13% (5–7), through venous ultrasonographic screening were 1–44% (5), and screening via venography were 13–50% (68). Table 1 highlights CVC characteristics that may lead to an increased VTE rate.…”
Section: Resultsmentioning
confidence: 99%
“…Ultrasound is the most common imaging modality employed to diagnose neonatal VTE, although venography is considered the reference standard for diagnosis of VTE (23). In the Canadian VTE registry study, Doppler ultrasound was used to diagnose 67% of the venous thromboses (11).…”
Section: Clinical Presentationmentioning
confidence: 99%
“…The availability of Doppler ultrasound as well as its non-invasive nature makes it an attractive diagnostic modality. However, it is operator dependent and its sensitivity and specificity decline when evaluating intrathoracic vessels as well as the iliac vessels or if the patient is edematous or has interfering skin abnormalities (23). A prospective study aimed at determining the incidence of asymptomatic venous thromboses associated with UVCs found that Doppler echocardiography was less sensitive than contrast venography (24).…”
Section: Clinical Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these episodes were clinically silent. In the PARKAA study (Prophylactic Antithrombin Replacement in Kids with ALL Treated with Asparaginase), ultrasound was demonstrated to be insensitive compared to venography for CVL-related intrathoracic thrombosis, but more sensitive for jugular vein thrombosis [11], suggesting that a combination of ultrasound and venograpy imaging is required for accurate diagnosis of CVL-related thrombosis in the upper venous system [12]. In the future, magnetic resonance imaging may become a noninvasive alternative for invasive venography for the detection of CVL-related thrombosis [13, 14].…”
Section: Frequency Of Cvl-related Thrombosismentioning
confidence: 99%